Stimulating Customer Inspiration Through Online Brand Community Climates: The Mediating Role of Customer Interaction - Cao, Yao; Zhou, Zhimin; Majeed, Salman (Frontiers in Psychology, 2021)
This study examines the impacts of the online brand community (OBC) climate on customer interaction and customer inspiration which are yet under-explored in the extant literature. Data were collected online from the Chinese respondents (N = 504) to analyze the proposed constructs of the study. Findings show that supportive OBC climate and controlled OBC climate are positively related to customer interaction (including information interaction and social interaction) and exert a significant and positive impact on customer inspiration. A mediating impact of customer interaction is found on the relationship between OBC climate and customer inspiration. This study unravels the importance and mechanism of customer-brand relationships in the online environment and illuminates pathways for marketers and policy makers to positively influence customer inspiration for business promotion. This study updates existing literature boxes of consumer behavior and marketing in the context of online customer-brand relationships. Limitations and future research directions are noted.